PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MTS NEGERI SAMBOJA KABUPATEN KUTAI KARTANEGARA - Nasuha . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The role of leadership in enhancing the teacher’s performance in MTsN Samboja Kutai Kartanegara is good. The many indicators to consider head’s role as manager; development of short term program, both academic or non-academic; mastering the materials of teaching; capability in managing the class; assessment and evaluation the strategy and teaching method.